Mass spectrometry imaging based on laser desorption ionization from inorganic and nanophotonic platforms - Samarah, Laith Z.; Vertes, Akos (View (Beijing, China), 2020)
Mass spectrometry imaging (MSI) has become an important analytical tool for the label‐free chemical imaging of diverse molecules in biological specimens. This minireview surveys some emerging methods in the context of factors that can lead to inaccurate information in MSI, chemical and spatial aberrations, along with their common sources. Matrix‐assisted laser desorption ionization, based on organic matrices, has become the most widely used MSI technique for biomolecules. However, due to inherent limitations associated with the use of organic matrices, for example, heterogeneous matrix‐analyte cocrystallization, and spectral interferences due to the matrix, laser desorption ionization (LDI) from inorganic and nanophotonic platforms has emerged as an alternative MSI modality with complementary advantages. In this review, inorganic and nanophotonic platforms for LDI‐MSI, their applications in imaging, notable merits, and limitations are described. Mass spectrometry imaging (MSI) by laser desorption ionization (LDI) based on inorganic and nanophotonic platforms is an emerging field that offers complementary advantages to conventional matrix‐assisted laser desorption ionization (MALDI). This mini‐review looks at the limitations of various MSI platforms in terms of the related spatial and chemical aberrations. Recent developments in inorganic substrates for LDI and nanophotonic ionization, for example, nanopost array platforms, are reported with emphasis on MSI.